State Regulation and the New Taylorism: The Case of Australian Grocery Warehousing - Lund, John; Wright, Christopher (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2001)
SummaryStudies of the diffusion of new workplace technologies and management practice often fail to account for differences in state labour regulation. This article examines the role of the state in seeking to regulate the introduction of an American system of computerized work monitoring in the Australian grocery warehouse industry. While the establishment of a government inquiry into the technology offered the potential for significant constraints upon management control, over time the state’s role shifted to a more accommodating stance that endorsed management’s right to use the new technology. The reasons underlying the state’s ultimate support for the technology are explored, as are the broader implications for national variations in the global diffusion of new workplace technologies.